Analisis Pengaruh Debt To Equity Ratio dan Current Ratio Terhadap Return On Assets pada PT Bukalapak Tbk Periode 2022-2024 (Jurnal Riset Manajemen dan Akuntansi, 2025)
English: This study aims to analyze the effect of Debt to Equity Ratio (DER) and Current Ratio (CR) on Return on Assets (ROA) at PT Bukalapak Tbk during the 2022-2024 period. A quantitative approach was employed using multiple linear regression and secondary data from quarterly financial statements. The partial test result indicate that DER and CR have no significant individual effect on ROA. Likewise, the simultaneous test result show that these variables together do not significantly affect ROA. The coefficient of determination (R²) value of 38,5% implies that DER and CR only partially explain the variation in ROA, with the remaining portion influenced by other factors outside the model. These findings suggest that in digital-based companies such as PT Bukalapak Tbk, profitability is not solely driven by capital structure and liquidity, but also by external dynamics such as business startegies,operational efficiency, and market conditions. This research is expected to serve as a reference for corporate management and investors in makingmore strategic and comprehensive financial decisions.